An ecological paradox: high species diversity and low position of the upper forest line in the Andean Depression - Peters, Thorsten; Bräuning, Achim; Münchow, Jannes; Richter, Michael (Ecology and Evolution, 2014)
Systematic investigations of the upper forest line (UFL) primarily concentrate on mid and high latitudes of the Northern Hemisphere, whereas studies of Neotropical UFLs are still fragmentary. This article outlines the extraordinary high tree diversity at the UFL within the Andean Depression and unravels the links between the comparatively low position of the local UFL, high tree-species diversity, and climate. On the basis of Gentry′s rapid inventory methodology for the tropics, vegetation sampling was conducted at 12 UFL sites, and local climate (temperature, wind, precipitation, and soil moisture) was investigated at six sites. Monotypic forests dominated by Polylepis were only found at the higher located margins of the Andean Depression while the lower situated core areas were characterized by a species-rich forest, which lacked the elsewhere dominant tree-species Polylepis. In total, a remarkably high tree-species number of 255 tree species of 40 different plant families was found. Beta-diversity was also high with more than two complete species turnovers. A non-linear relationship between the floristic similarity of the investigated study sites and elevation was detected. Temperatures at the investigated study sites clearly exceeded 5.5°C, the postulated threshold value for the upper tree growth limit in the tropics. Instead, quasi-permanent trade winds, high precipitation amounts, and high soil water contents affect the local position of the UFL in a negative way. Interestingly, most of the above-mentioned factors are also contributing to the high species richness. The result is a combination of a clearly marked upper forest line depression combined with an extraordinary forest line complexity, which was an almost unknown paradox.

Coupling ordination techniques and GAM to spatially predict vegetation assemblages along a climatic gradient in an ENSO-affected region of extremely high climate variability - Münchow, Jannes; Feilhauer, Hannes; Bräuning, Achim; Rodríguez, Eric Frank; Bayer, Fabian; Rodríguez, Rodolfo Arismendiz; von Wehrden, Henrik (Journal of Vegetation Science, 2013)
Questions: El Niño Southern Oscillation (ENSO) is a strong driver of climatic and ecosystem variability in coastal NW Peru. La Niña amplifies the already dry local conditions, and led to depleted ecosystems in 2011. However, the 2012 La Niña event triggered rainfall far above the average. (1) Did plant species diversity, primary productivity and vegetation assemblages change along a climatic gradient between two climatologically different La Niña years; (2) Is there a difference in explanatory power of environmental predictors between the 2 yr; and (iii) is it possible to predict the observed vegetation patterns spatially? Location: Transect along a climatic gradient in the Sechura Desert of Piura, NW Peru (corresponds to the terrestrial part of the El Niño region 1 + 2) - a region of extremely high climatic variability. Methods: We visited 50 30 m × 30 m randomly sampled plots in 2011 and 2012. A Procrustes analysis of two non-metric multidimensional scaling (NMDS) ordinations provided information on the temporal change of species assemblages. Variation partitioning revealed the differences in explanatory power of the predictors. We employed a generalized additive model (GAM) to fit the scores of the first ordination axis with a floristic gradient map as a result. Results: Generally, higher rainfall resulted in a positive feedback when considering biodiversity, productivity and vegetation assemblages. The floristic gradient map resulting from the GAM displayed the spatial distribution of the three main assemblages along the climatic gradient. Edaphic variables added no independent portion to the explanation of the vegetation assemblages, but explained in conjunction with topography and NDVI a considerable amount of the variance. Conclusions: Strong Atlantic easterly winds crossing the Andes can boost plant growth even during a La Niña situation. This underscores the need for a deeper understanding of ENSO-related climate variability of ENSO. Combining vegetation maps with accurate predictions of such climatic anomalies would aid the effective execution of conservation and recovery strategies. Additionally, coupling an unconstrained ordination with a GAM appears to be a promising tool for vegetation mapping, especially in the presence of a non-linear gradient.
Keywords: Edaphic gradient; Multivariate statistics; Precipitation gradient; Species distribution; Tropical dry forest; Vegetation unit distribution

Predictive mapping of species richness and plant species' distributions of a peruvian fog oasis along an altitudinal gradient - Münchow, Jannes; Bräuning, Achim; Rodríguez, Eric Frank; von Wehrden, Henrik (Biotropica, 2013)
Tropical arid to semi-arid ecosystems are nearly as diverse as more humid forests and occupy large parts of the tropics. In comparison, however, they are vastly understudied. For instance, fog precipitation alone supports a unique vegetation formation, locally termed lomas, on coastal mountains in the Peruvian desert. To effectively protect these highly endemic and threatened ecosystems, we must increase our understanding of their diversity patterns in relation to environmental factors. Consequently, we recorded all vascular species from 100 random 4 × 4 m plots on the fog-exposed southern slope of the mountain Mongón. We used topographic and remotely sensed covariates in statistical models to generate spatial predictions of alpha diversity and plant species' distribution probabilities. Altitude was the most important predictor in all models and may represent fog moisture levels. Other significant covariates in the models most likely refer also to water availability but on a finer spatial scale. Additionally, model-based clustering revealed five altitudinal vegetation zones. This study contributes to a better spatial understanding of the biodiversity and spatial arrangement of vegetation belts of the largely unknown but highly unique lomas formations. Furthermore, mapping species richness and plant species' distributions could support a long-needed lomas strategic conservation scheme. © 2013 Association for Tropical Biology and Conservation Inc.
Keywords: Biodiversity conservation; Climatic gradient; El Niño Southern Oscillation (ENSO); La Niña; lomas; Species distribution models; Species richness model; Tropical plant diversity

Relationships between ring width and maximum latewood density – an example from southeast Tibet - Hochreuther, Philipp; Münchow, Jannes; Grießinger, Jussi; Bräuning, Achim (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 11: Proceedings of the DENDROSYMPOSIUM 2012 Scientific Technical Report STR13/05, GFZ Potsdam, 2013)

Soil texture and altitude, respectively, largely determine the floristic gradient of the most diverse fog oasis in the Peruvian desert - Münchow, Jannes; Hauenstein, Simon; Bräuning, Achim; Bäumler, Rupert; Rodriguez, Eric Frank; Von Wehrden, Henrik (Journal of Tropical Ecology, 2013)
Studying species turnover along gradients is a key topic in tropical ecology. Crucial drivers, among others, are fog deposition and soil properties. In northern Peru, a fog-dependent vegetation formation develops on mountains along the hyper-arid coast. Despite their uniqueness, these fog oases are largely uninvestigated. This study addresses the influence of environmental factors on the vegetation of these unique fog oases. Accordingly, vegetation and soil properties were recorded on 66 4 × 4-m plots along an altitudinal gradient ranging from 200 to 950 m asl. Ordination and modelling techniques were used to study altitudinal vegetation belts and floristic composition. Four vegetation belts were identified: a low-elevation Tillandsia belt, a herbaceous belt, a bromeliad belt showing highest species richness and an uppermost succulent belt. Different altitudinal levels might reflect water availability, which is highest below the temperature inversion at around 700 m asl. Altitude alone explained 96% of the floristic composition. Soil texture and salinity accounted for 88%. This is in contrast with more humid tropical ecosystems where soil nutrients appear to be more important. Concluding, this study advances the understanding of tropical gradients in fog-dependent and ENSO-affected ecosystems. © Cambridge University Press 2013.
Keywords: altitudinal zonation; diversity gradient; dry tropics; edaphic gradient; ENSO; floristic modelling; La Niña; South America; spatial analysis; species richness